2020
DOI: 10.3390/cells9020447
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Anti-Proliferative GPER Inverse Agonist ERα17p with the Breast Cancer Cell Plasma Membrane: From Biophysics to Biology

Abstract: The peptide ERα17p, which corresponds to the 295-311 fragment of the hinge/AF2 domains of the human estrogen receptor α (ERα), exerts apoptosis in breast cancer cells through a mechanism involving the G protein-coupled estrogen-dependent receptor GPER. Besides this receptor-mediated mechanism, we have detected a direct interaction (Kd value in the micromolar range) of this peptide with lipid vesicles mimicking the plasma membrane of eukaryotes. The reversible and not reversible pools of interacting peptide may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…This peptide acts as a GPER inverse agonist and shows anti-proliferative effects in breast cancer cells and a decrease in the volume of breast tumors in xenografted mice (63). The N-terminal PLMI motif of this peptide presents some chemical analogies with the GPER antagonist PBX1 and exerts the same anti-proliferative potency as the whole length peptide (25,62), suggesting strongly that this region corresponds to the active motif. Due to the large number of rotatable bonds in ERα17p, MD simulations were necessary to map the conformational landscape of the receptorpeptide molecular system.…”
Section: The Current Area Of Computational Methods For Studying Gpermentioning
confidence: 94%
See 1 more Smart Citation
“…This peptide acts as a GPER inverse agonist and shows anti-proliferative effects in breast cancer cells and a decrease in the volume of breast tumors in xenografted mice (63). The N-terminal PLMI motif of this peptide presents some chemical analogies with the GPER antagonist PBX1 and exerts the same anti-proliferative potency as the whole length peptide (25,62), suggesting strongly that this region corresponds to the active motif. Due to the large number of rotatable bonds in ERα17p, MD simulations were necessary to map the conformational landscape of the receptorpeptide molecular system.…”
Section: The Current Area Of Computational Methods For Studying Gpermentioning
confidence: 94%
“…The results pointed out to a functional crosstalk and a cross-stimulation between GPER and AhR. Computational methods have also been used to investigate the binding to GPER of the peptide ERα17p, which encompasses a part of the hinge region/AF2 domain of the human ERα ( 25 , 62 ). This peptide acts as a GPER inverse agonist and shows anti-proliferative effects in breast cancer cells and a decrease in the volume of breast tumors in xenografted mice ( 63 ).…”
Section: The Current Area Of Computational Methods For Studying Gpermentioning
confidence: 99%
“…These selective modulators of GPER have been used in over 200 studies to evaluate GPER actions in a variety of cellular and animal models. More recently, a first peptide GPER ligand corresponding to part of the hinge region/AF2 domain of the human ERα was identified, which acts as an inverse agonist of GPER to suppress mitogenic signaling and inhibit breast cancer cell growth (105,106). In addition, two novel GPER specific agonists, GPER-L1 and GPER-L2, were synthesized in 2012 with binding affinities of ∼100 nM (107).…”
Section: Gper Ligandsmentioning
confidence: 99%
“…As few years later, further experimental data showed that in breast cancer cells the synthetic molecule MIBE may bind to and block both ERα and GPER1 activity [ 61 ]. More recently, it has been identified the first peptide GPER1 ligand, termed ERalpha17p, corresponds to a portion of the hinge region/AF2 domain of the human ERα [ 65 , 66 ]. ERalpha17p shows an anti-tumoral activity in breast cancer cells [ 65 , 66 ].…”
Section: Gper1 Ligands and Signallingmentioning
confidence: 99%
“…More recently, it has been identified the first peptide GPER1 ligand, termed ERalpha17p, corresponds to a portion of the hinge region/AF2 domain of the human ERα [ 65 , 66 ]. ERalpha17p shows an anti-tumoral activity in breast cancer cells [ 65 , 66 ].…”
Section: Gper1 Ligands and Signallingmentioning
confidence: 99%